Severity of an uncharacteristically large wildfire, the Rim Fire, in forests with relatively restored frequent fire regimes - Lydersen, Jamie M.; North, Malcolm P.; Collins, Brandon M. (Forest ecology and management, 2014)
•Pre-fire field data was used to assess Rim Fire severity in frequent-fire forests.•Regardless of forest conditions, plume-dominated fire burned at higher severity.•Under less extreme weather, fire severity was mainly low or moderate.•Shrubs, time since last fire, elevation and burning index were related to severity. The 2013 Rim Fire, originating on Forest Service land, burned into old-growth forests within Yosemite National Park with relatively restored frequent-fire regimes (⩾2 predominantly low and moderate severity burns within the last 35years). Forest structure and fuels data were collected in the field 3–4years before the fire, providing a rare chance to use pre-existing plot data to analyze fire effects. We used regression tree and random forests analysis to examine the influence of forest structure, fuel, fire history, topographic and weather conditions on observed fire severity in the Rim Fire, as estimated from an initial fire severity assessment based on the relative differenced normalized burn ratio (RdNBR). Plots that burned on days with strong plume activity experienced moderate- to high-severity fire effects regardless of forest conditions, fire history or topography. Fire severity was also highly negatively associated with elevation, with lower severity observed in plots over 1700m. Burning index (a composite index of fire weather), time since the last fire, and shrub cover had strong positive associations with fire severity. Plots that had experienced fire within the last 14years burned mainly at low severity in the Rim Fire, while plots that exceeded that time since last fire tended to burn at moderate or high severity. This effect of time since last fire was even more pronounced on days when the burning index was high. Our results suggest that wildfire burning under extreme weather conditions, as is often the case with fires that escape initial attack, can produce large areas of high-severity fire even in fuels-reduced forests with restored fire regimes.